Enhancing Cadet Preparedness For Engine Maintenance Challenges: A Qualitative Study In Maritime Education - Baihaqi Baihaqi (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This qualitative study investigates the challenges faced by new engine officers in maritime settings, focusing on their transition from theoretical learning to practical engine maintenance. Through semi-structured interviews with experts in marine engineering and engine management, the research identifies significant gaps between theoretical knowledge acquired in classrooms and the practical skills required aboard ships. Key findings highlight the need for educational reforms, including increased practical training hours, curriculum adjustments to enhance relevance, and integration of simulation technologies. Participants, comprising professional engine masters, endurance managers, and maritime educators, unanimously advocate for a more hands-on approach to training that prepares cadets to handle complex engine maintenance tasks effectively. Simulation technologies, particularly virtual reality simulations, emerge as crucial tools for bridging the gap between theory and practice. They provide realistic environments for cadets to simulate diverse operational scenarios and develop critical decision-making skills without exposing them to actual risks. The study concludes with recommendations for collaborative efforts between educational institutions and industry stakeholders to implement these reforms, ensuring a competent and prepared workforce capable of meeting the dynamic challenges of modern maritime operations.